Ištar and the motif of the cosmological warrior: Assurbanipal’s adaptation of Enuma elish - Crouch, C.L. (Eisenbrauns, 2013)
Esarhaddon and Assurbanipal are well known to scholars of ancient Near Eastern prophecy, thanks to their affinity for prophecy and the prophetic goddess Ištar in particular, which resulted in the preservation of oracular material in a manner not attested for other Sargonid kings. It has been suggested that one of the reasons for this affinity was the reliance of both kings on prophetic legitimation to buttress their contested claims to kingship. This paper explores how Assurbanipal in particular also relies on Ištar to legitimate his military activities, also as a result of the difficult political circumstances in which he was obliged to operate. This legitimation takes the form of allusion to Enuma Elish and the accrual of the characteristics of its warrior hero to the goddess Ištar.